1995
DOI: 10.1111/j.1600-051x.1995.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of endodontic infection on progression of marginal bone loss in periodontitis

Abstract: The purpose of the present investigation was to determine magnitude and rate of proximal radiographic attachment loss in relation to endodontic infection in periodontally involved teeth. The investigation was conducted as a retrospective longitudinal study on a periodontitis-prone randomly selected referral population, including 175 single-rooted, root-filled teeth in 133 patients. An observation period of at least 3 years was required. Periapical conditions of the selected sample at baseline and re-examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 15 publications
8
64
1
3
Order By: Relevance
“…We found that the severity of marginal bone loss was positively correlated with the number and size of periapical radiolucencies. This finding is consistent with those of Jansson et al (33) and Ehnevid et al (34).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the severity of marginal bone loss was positively correlated with the number and size of periapical radiolucencies. This finding is consistent with those of Jansson et al (33) and Ehnevid et al (34).…”
Section: Discussionsupporting
confidence: 91%
“…As was previously shown (33,34), periodontal disease measures appeared to influence endodontic treatment outcomes. Of the 3,533 teeth examined in this study, 11% had severe marginal bone loss.…”
Section: Discussionmentioning
confidence: 54%
“…In a retrospective study, periodontal problem constituted 32% of the failures of post-endodontic teeth, which was even higher than the 8.6% of failures due to endodontic causes (Vire, 1991). Decay and trauma responsible to pulpitis, and irritation from endodontic medicates and filling materials have been attributed to the co-existence of periodontal disease (Jansson et al, 1995;Timmerman and Van der Weijden, 2006). Numerous investigations have reported the impact of the periodontal status on the survival of endodontically treated teeth (Komada et al, 2006;Naumann et al, 2006;Reinhardt et al, 1983).…”
Section: Introductionmentioning
confidence: 97%
“…The pathways for the spread of bacteria between pulpal and periodontal tissues have been discussed with controversy. [1,2,3] Pulpal infection can drain through the periodontal ligament space and give an appearance of periodontal destruction, termed retrograde periodontitis. Similarly, both pulpal and periodontal infections can coexist in the same tooth, termed combined lesions, where the treatment depends on the degree of involvement of the tissues.…”
Section: Introductionmentioning
confidence: 99%